Features of matrix metalloproteinases MMP2, MMP3, MMP9 genes regulatory region polymorphism in patients with uterine fbroids - A. V. Shevchenko; V. F. Prokofev; V. I. Konenkov; Yu. S. Timofeeva; E. G. Koroleva; I. O. Marinkin; S. V. Aidagulova (Сибирский научный медицинский журнал, 2023)
Violation of the extracellular matrix components synthesis regulation contributes to the formation and growth of uterine fbroids (MM). Changes of collagen metabolism in connective tissue may be associated with polymorphism of matrix metalloproteinase (MMP) genes. Aim of the study was to analyze of the association of regulatory regions of matrix metalloproteinase genes MMP2 (rs243865), MMP3 (rs3025058), MMP9 (rs3918242) with the development of uterine myoma, its histological form, several concomitant gynecological diseases. Material and methods. The clinical study of 69 patients (23–54 years old) with uterine myoma was conducted. According to the anamnesis, 57.9 % of patients had childbirth, 46.4 % of women had an artifcial termination of pregnancy, and 15.9 % of women had endometriosis. In histological examination, in 48.14 % the nodes corresponded to the phenotype of simple fbroids with a large proportion of fbrous tissue, 51.6 % with the phenotype of proliferating fbroids. The comparison group is represented by a random population sample of women from Western Siberia. 183 women without pronounced gynecological pathologies were examined. MMP2-1306 C/T polymorphism was analyzed by TaqMan, MMP3-1171 5A/6A, MMP9-1562 C/T by restriction fragment length polymorphism method. Results. The genotype frequencies of the analyzed genes did not signifcantly diﬀer between the groups. The complex genotype MMP2-1306CC:MMP3-11715A6A:MMP9-1562CT was decreased in women with uterine myoma relative to the persons of the comparison group. In endometriosis patients MMP9-1562CC genotype was reduced and heterozygosity was increased relative to patients without endometriosis. The frequency of MMP2-1306CC:MMP9-1562CT complex genotype is signifcantly higher in women who gave birth than in women who did not give birth. Complex genotypes diﬀerences between histological variants of uterine myoma were revealed. Conclusions. The results of the study show the signifcance of polymorphism eﬀect of the regulatory regions of the MMP genes in the development and nature of the course of uterine myoma.